Use of nonaversive handling and training procedures for laboratory mice and rats: Attitudes of American and Canadian laboratory animal professionals - O'Malley, Carly I.; Hubley, Raina; Moody, Carly; Turner, Patricia V. (Frontiers in Veterinary Science, 2022)
Nonaversive or low stress handling (LSH) techniques can reduce fear and stress in research rodents, ultimately improving study data quality. Uptake of LSH has been slow in the USA and Canada. In this study we explored the understanding, experience, and attitudes towards LSH of rats and mice in laboratory animal professionals from the USA (US) and Canada (CA). Participants (n=40) were recruited for a standardized interview and job categories were divided into veterinary/PhD level roles (doctoral level; DL) and non-veterinary/non-PhD level roles (non-doctoral level, NDL) (US: 23, DL: 9, NDL: 14; CA: 17, DL: 8, NDL: 9). Interviews were transcribed and analyzed using NVIVO. Two research assistants independently coded themes for each question and consolidated responses based on commonality. Laboratory animal professionals understood the benefits of LSH and training techniques with rats and mice, stating reduced stress, better data, and improved welfare, with CA participants more likely to mention animal welfare as a benefit, and DL more likely to mention improved research data and reduced stress. Participants across demographic groups indicated improved job satisfaction and decreased stress as the positive impacts LSH would have on their positions. The primary perceived barriers to LSH implementation were researcher attitudes, the time needed to implement and use these techniques, and training personnel to use the techniques properly and consistently. To promote refinement of handling of rats and mice, more educational opportunities on the benefits and implementation of LSH techniques need to be provided to laboratory animal professionals, as well as to researchers.